Post-perceptual processing during the attentional blink is modulated by inter-trial task expectancies - Sy, Jocelyn L.; Elliott, James C.; Giesbrecht, Barry (Frontiers in Human Neuroscience, 2013)
The selective processing of goal-relevant information depends on an attention system that can flexibly adapt to changing task demands and expectations. Evidence from visual search tasks indicates that the perceptual selectivity of attention increases when the bottom-up demands of the task increase and when the expectations about task demands engendered by trial history are violated. Evidence from studies of the attentional blink (AB), which measures the temporal dynamics of attention, also indicates that perceptual selectivity during the AB is increased if the bottom-up task demands required are increased. The present work tested whether expectations about task demands engendered by trial history also modulate perceptual selectivity during the AB. Two experiments tested the extent to which inter-trial switches in task demands reduced post-perceptual processing of targets presented during the AB. Experiment 1 indexed post-perceptual processing using the event-related potential (ERP) technique to isolate the context sensitive N400 ERP component evoked by words presented during the AB. Experiment 2 indexed post-perceptual processing using behavioral performance to determine the extent to which personal names survive the AB. The results of both experiments revealed that both electrophysiological (Exp. 1) and behavioral (Exp. 2) indices of post-perceptual processing were attenuated when consecutive trials differed in terms of their perceptual demands. The results are consistent with the notion that the selectivity of attention during the AB is modulated not only by within-trial task demands, but also can be flexibly determined by trial-by-trial expectations.